The Sufi Who Was a Sayyid: Muḥammad Ḥusaynī Gesūdarāz’s Assertions of Spiritual Authority - Malik, Pia Maria (Medieval encounters, 2023)
In the context of contested succession within a silsila (lineage) of sufis, this paper studies Sayyid Muḥammad Ḥusaynī Gesūdarāz’s (d. 1422) recourse to a familial genealogy in order to claim the status of a pīr or sufi master, while attempting to entrench his legacy in Gulbarga where he emigrated to from Delhi after the incursions of Timur (d. 1405). As he arrived in the Deccan at the turn of the fifteenth century, Gesūdarāz used his kinship with the Prophet and particularly his identity of sayyid (a descendant of the Prophet through Ḥusayn) as a persuasive device, to set himself apart from other sufi shaykhs in the area who claimed an equivalent spiritual genealogy. The case of Gesūdarāz reveals a societal pattern wherein the identity of sayyid was gaining new traction, and relational ties were evoked not only as a means of establishing an identity as part of a community but also to supersede others who made the same claim. Kinship was a device through which Gesūdarāz staked his claim to authority, and it was also a mechanism that he and his family utilized to cement their hold on the Muslim community of Gulbarga.